APPLYING A NON-PARAMETRIC EFFICIENCY ANALYSIS TO EVALUATE FARM ECONOMIC VIABILITY - Miljatović, Aleksandar; Vukoje, Veljko; Tekić, Dragana (Journal on Processing and Energy in Agriculture, 2022)
The aim of this research is to investigate technical efficiency in different types of farming in Republic of Serbia and then to determine achieved level of farm economic viability. The research is based on FADN data from 2020 year. An input-oriented data envelopment analysis method with variable return to scale is used for calculating farm technical efficiency. One output and four input variables are used in the model. Research has shown that farm technical efficiency in Serbia is on relatively low level (0.346). This indicates that there are significant reserves for potentially input reduction, without output reducing. According to types of farming the most efficient farms are the ones involved in horticulture production (0.542), followed by granivores (0.458) and vineyards and fruits (0.433), while the least efficient are dairy production (0.292). It is noticeable that more intensive types of farming have better output-input ratio, which indicates that those farms reached higher economic viability level. Of course, farm economic viability is wider term and further research should be directed at one comprehensive farm economic viability analysis which would take into consideration other relevant productivity indicators as well as profitability, liquidity and stability indicators. Thereby, considering FADN base limitations that are particularly noticeable when calculate liquidity and stability indicators, is necessary to continuously work on data quality improvement and to make the whole system better.